BIOCONCENTRATION FACTORS OF HEAVY METALS COPPER (CU) AND ZINC (ZN) IN GREEN MUSSELS (Perna viridis) IN THE WATERS OF TAMBAK LOROK SEMARANG - Jihan Najla Difa; Max Rudolf Muskananfola; Churun A’in (Jurusan Perikanan dan Kelautan, 2022)
Tambak Lorok is a coastal area in Semarang. These waters have the potential to be contaminated with heavy metals Copper (Cu) and Zinc (Zn). The study aimed to determine the concentration of Cu and Zn in water, sediment and soft tissues of Perna viridis, knowing the effect of shell size on heavy metal absorption, knowing the bioconcetration factors of heavy metals and knowing the maximum limit of weekly consumption of Perna viridis. The study was conducted in November 2020. Determination of the location of the study using the Purposive sampling method.Concentrations of Cu and Zn in water, sediment and Perna viridis by the Atomic Absorption Spectrophotometer method. The results showed the content of Copper in water ranged from 0.06-0.151mg/l; sediments 26.634-38.433 mg/l and green mussels 4.76-11.00mg/l. Heavy metal Zinc is not detected in water, sediment and green shells one factor is that the tools used are insensitive to low concentrations of metals. Based on the results of statistical tests the difference in shell size has no effect on the absorption of Cu in soft tissues. Bioaccumulation levels belong to the low-moderate category. The safe limit of consumption of green mussels for weight 40 kg is 15.683 mg/weeks and for weight 60 kg is 23.524 mg/weeks.